Climate change threat on socio-economic condition of agroforestry managers: A vulnerability study in eastern Himalayan state of Mizoram, Northeast India - Uttam Thangjam; Pentile Thong; Uttam Kumar Sahoo (Climate Risk Management, 2023)
In recent years, the increase in transition from shifting cultivation to permanent agroforestry (AF) plantations such as oil palm, Areca nut etc. in Mizoram, Northeast India has made the present study all the more essential with regard to social, economic and ecological perspective. Four most prominent AFSs i.e., Parkia based AFS (PAFS), Areca based AFS (AAFS), Oil palm based AFS (OAFS) and Borrasus based AFS (BAFS) were selected for the vulnerability assessment in the tribal state of Mizoram, North-East India (NEI). The association between AF managers and their physical and social surroundings was extensively integrated and analysed to assess the Socio-economic Vulnerability Index (SeVI). This vulnerability assessment involved data normalization, factor analysis, weight assignment, and finally index calculation. 10% household from each of the six villages were sampled to identify the target AFSs following which 78 indicators under 15 domain groups and 3 dimensions were perceived to be apt for this study. AF managers practicing BAFS (0.65) was found to be most vulnerable to climate change followed by OAFS (0.63), AAFS (0.57) and PAFS (0.43). For the dimensions of vulnerability BAFS scored maximum (0.98) for adaptive capacity and OAFS for sensitivity (0.49) and exposure (0.48). While the most vulnerable among domains were: “demographic” for adaptive capacity, “AF function” for sensitivity and “impact on crop varieties” for exposure. Although the IPCC considered AF as an important for climate change, to bridge the gap by adapting new measures for the managers is needed to make them socio-economically less vulnerable henceforth.